“Can You Be a Fair and Impartial Juror?”: Pro-Police Bias in the Courtroom - Page, Andrew N. (Tufts Archival Research Center, 2015)
Abstract: In a trial, occasionally a police eyewitness and a civilian eyewitness disagree on the facts of the case and it is left to the jury to determine which version of events is more reliable and which witness is more credible. Past studies show that it is not uncommon for jurors to have preconceived biases (and they often mask these biases with casuistry), and that jurors put a great amount of weight on eyewitness testimony. Jurors also place a high amount of credibility on police officers, even though it has been shown that police officers are often just as fallible as civilians. However, these beliefs may also vary depending on the juror and his or her ethnic group. An experiment was run on 89 students from Tufts University to determine if jurors are more likely to find a defendant guilty when a police officer testifies for the prosecution (and a civilian testifies for the defense) and if a more explicit juror reminder can be given to mitigate any preconceived biases toward or against police officers. Four groups of participants read the summary of a mock trial, which varied depending on the status of one witness and the type of reminder given to the jury. Results did not reach statistical significance, although promising trends did arise, suggesting that a more explicit reminder increases the likelihood that a juror will find a defendant guilty, and the status of one witness (and its interaction with a reminder to the jury) can affect the perception of other witnesses, as seen through ratings of persuasion. Future directions are discussed, and strongly recommended, in hopes of the observed trends reaching statistical significance.